Viscosity evaluation for glass and glass crystal compositions in their foaming temperature range - Kazmina O. V. Olga Viktorovna; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Abiyaka A. N.; Popletneva Yu. V. (2009, 2009)
A method is proposed and used to calculate the viscosity of glass and glass crystal compositions in the foaming temperature range. It is determined that for the glass phase content lower than 75% the viscosity of a glass crystal composition depends on the ratio of the crystal and glassy phases and for glass phase content higher than 75% the viscosity of the composition and foaming ratio are determined mainly by the composition of the glass phase